PERAN DINAS PERINDUSTRIAN DAN PERDAGANGAN DALAM MEMBINA INDUSTRI KECIL MENENGAH (IKM) PEREKONOMIAN MASYARAKAT KABUPATEN SERDANG BEDAGAI - Muktarruddin; Mirzaya, Ilham; Nasution, Syafiratunnisa (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2023)
In general, the aim of this research is to determine the role of the Department of Industry and Trade in developing small and medium industries in the economy of the people of Serdang Bedagai Regency. As well as what the condition of SMEs there is, and also the challenges faced by the department and industry players in developing the community economy in Serdang Berdagai. This type of research is qualitative with a qualitative descriptive approach method to obtain an in-depth picture (description). Data was obtained through interviews, documentation studies and observations. The research informants consisted of five, namely: the Head of the Department of Industry and Trade, Serdang Berdagai Regency, his Secretary, Industrial Staff, and two SMEs. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of the research show that the role played by the Department of Industry and Trade is quite influential in developing the Small and Medium Industry community in Serdang Berdagai Regency. With the state of Small and Medium Industries recorded in 1985 there were industries in Serdang Berdagai Regency. There are many roles created by the Department as facilitators, regulators and catalysts, where these roles include helping SMEs to improve the community's economy. However, it is inevitable that there will be obstacles that occur, the obstacles found in the field are a lack of insight into technology, limited community personnel from the Department of Industry and Trade and limited sources of capital.